Implementing blended first-year chemistry in a developing country using online resources - Reyes, Charisse Tongson; Kyne, Sara Helen; Lawrie, Gwendolyn Angela; Thompson, Christopher David (Online learning (Newburyport, Mass.), 2022)
Decades of rapid development in information and communication technologies (ICTs) have resulted in tremendous global evolution in computer and online instruction. Many developing countries, however, are still struggling to successfully integrate ICTs in their teaching and learning practices, subsequently leading to slower rates of adapting digital learning pedagogies. To understand how blended instruction might operate in higher education in a developing country, this study explored students’ perspectives on the implementation of blended learning in a first-year chemistry program delivered in the Philippines. Through the resource-based learning framework, multiple types of online learning resources were employed for blended delivery of topics on periodic trends, chemical bonding, Lewis structures, molecular shape and polarity through the learning management system, Moodle. To understand the students’ experiences, a mixed methods approach was employed through a survey, focus groups, and learning analytics. Despite the scarcity of technological resources (such as access to a reliable internet connection) 57.5% of 447 student respondents favoured blended learning because of the flexibility, wider access to different types of interactive learning resources, variety of learning activities, and perceived increase in learning productivity. While the majority of respondents (75.7%) had ICT skills sufficient for education, much fewer had access to computers (19.7%). 40.0% of students self-reported that they preferred a traditional mode of instruction primarily due to the perceived difficulty of chemistry as subject matter and the students’ perceived need for a physically-present teacher to explain concepts face-to-face and to respond to questions that would arise anytime during the learning period.